KONTRAKT SPÓŁKI JAKO ALTERNATYWNA DLA POŻYCZKI MORSKIEJ FORMA PRAWNA FINANSOWANIA HANDLU MORSKIEGO - Benincasa, Zuzanna (Zeszyty Prawnicze, 2016)
THE CONTRACT OF PARTNERSHIP AS AN ALTERNATIVE FOR THE MARITIME LOAN FORM OF FINANCING OF MARITIME COMMERCE Summary The best known form of a common investment in maritime trading was a contract of maritime loan. On the basis of this contract the creditor undertook the risk of the perishing of the ship (periculum maris) in which case he was not entitled to claim his money back, but as a reward he could stipulate the interests exceeding the legal rate in case of a successful journey. Analogical purposes could be realized through making the consensual contract of societas, in case of concluding of a partnership in which only one partner made a contribution of capital and the other socius \contributed his future services that consisted of travelling and trading and as the consequence was exposed to the risk of navigation. The willingness to undertake such a risk, was treated as a very precious component of a partner’s services and in case of a partnership in which only one partner made such a contribution, his contribution was deemed to be of extreme value and importance and thus justify granting him a special position in a partnership that means being excluded from bearing the loss of capital contributed by other socius. The question of the exclusion of one of the partners from bearing the loss constituted one of the issues of the controversy reported in legal sources as magna questio. This controversy is deemed to be related with the transformation of a partnership from the community of properties to a modern kind of partnership being an instrument of conducting economic activities and gaining profits. In the latter the partners did not necessarily create a co-ownership of their properties as their contributions were made quo ad usum. In this kind of partnership also a contribution consisting of future services was very often more important for making profit than a monetary contributions. The heroes of the controversy were two famous republican jurists Quintus Mucius Scaevola and Servius Sulpicius Rufus. The controversy between these two jurists regarded the possibility of making a partnership in which one partner was to have a minor share in the loss in respect of his share in the profit. The pactum on the basis of which one of the partners was to have the minor share in the loss in respect of his share in profit was deemed by Quintus Mucius to be contra naturam societatis, but for his adversary it was possible to make such a partnership and it was even possible to exclude one of the partners from bearing the loss resulted from the partnership’s business. According to Servius such an agreement was valid if such a partner contributed only with his services in the partnership and these services as crucial for partnership’s business were deemed to be of the same value as the capital contributed by the other partners. Servius’ intent was thus to prevent the situation in which the partner who offers only his services for a partnership was obliged to take part in the loss of the capital contributed by other partners.